2013
DOI: 10.4238/2013.november.22.16
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Anatolian traditional quince cultivars, based on microsatellite markers

Abstract: ABSTRACT. We conducted simple sequence repeat (SSR) analyses of 15 traditional quince (Cydonia oblonga) cultivars from Anatolian gene sources for molecular characterization and investigation of genetic relationships. Three pear and two apple cultivars were used as references for SSR locus data analysis and to determine allele profiles between species. Eight SSR loci that were developed from apple and pear were used, and a total of 44 alleles were found among quince cultivars. The CH01F02 locus was found to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Kafkas et al (2015) also showed the presence of genetic variability when 40 quince accessions from Turkey were characterized using amplified fragment length polymorphism markers. Yuksel et al (2013) performed molecular analyses in 15 traditional quince cultivars and found a similar relationship between 18% and 87% among cultivars.…”
Section: Resultsmentioning
confidence: 91%
“…Kafkas et al (2015) also showed the presence of genetic variability when 40 quince accessions from Turkey were characterized using amplified fragment length polymorphism markers. Yuksel et al (2013) performed molecular analyses in 15 traditional quince cultivars and found a similar relationship between 18% and 87% among cultivars.…”
Section: Resultsmentioning
confidence: 91%
“…Quince, which is the other plant we used in this study (Cydonia oblonga), belongs to the family Rosaceae and Turkey is one of the most important quince producers worldwide (34). Leaf, fruit and seed of quince have very important medicinal effects.…”
Section: Discussionmentioning
confidence: 99%
“…According to a number of published studies, additional SSR markers that have been isolated from apple and pear also work with quince (see, for example, Xuan et al., 2013; Yamamoto et al., 2004; Yüksel et al., 2013).…”
Section: Markers In Selected Species Of Fruit Cropmentioning
confidence: 99%